Militairen beveiligen vuilniskar op Spiegelgracht. Uit: archief F. Domela Nieuwenhuis, VI a 1B,no.28. Originele foto: BG A61/175
Militairen beveiligen vuilniskar op Spiegelgracht. Uit: archief F. Domela Nieuwenhuis, VI a 1B,no.28. Originele foto: BG A61/175.